2018
DOI: 10.1037/xge0000368
|View full text |Cite
|
Sign up to set email alerts
|

Reasons probably won’t change your mind: The role of reasons in revising moral decisions.

Abstract: Although many philosophers argue that making and revising moral decisions ought to be a matter of deliberating over reasons, the extent to which the consideration of reasons informs people's moral decisions and prompts them to change their decisions remains unclear. Here, after making an initial decision in 2-option moral dilemmas, participants examined reasons for only the option initially chosen (affirming reasons), reasons for only the option not initially chosen (opposing reasons), or reasons for both opti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 64 publications
3
52
4
1
Order By: Relevance
“…There might, however, be other differences between more general moral judgements and blame judgements, for example in adjustment size, which we did not explicitly assess here. Our findings starkly contrast with other previous research studying updating that reports rare and small judgement adjustments (Baron & Gürçay, 2017;Gürcay & Baron, 2017;Koop, 2013;Stanley et al, 2017). For instance, we found changes in moral judgement valence to occur in 22.3% of the trials on average, whereas these studies reported 1.2-4.8%.…”
Section: Adjustment Of Judgements After Learning Contextual Informationcontrasting
confidence: 99%
See 1 more Smart Citation
“…There might, however, be other differences between more general moral judgements and blame judgements, for example in adjustment size, which we did not explicitly assess here. Our findings starkly contrast with other previous research studying updating that reports rare and small judgement adjustments (Baron & Gürçay, 2017;Gürcay & Baron, 2017;Koop, 2013;Stanley et al, 2017). For instance, we found changes in moral judgement valence to occur in 22.3% of the trials on average, whereas these studies reported 1.2-4.8%.…”
Section: Adjustment Of Judgements After Learning Contextual Informationcontrasting
confidence: 99%
“…Decision reversals were rare, occurring between 1.2 -4.8% of all trials. Another study investigated moral judgement updating when participants were presented with reasons opposing the initial judgement (Stanley, Dougherty, Yang, Henne, & De Brigard, 2017). The authors reported that people rarely changed their initial judgement after considering the provided reasons.…”
Section: Moral Judgment Updatingmentioning
confidence: 99%
“…In contrast to such approaches, experimental moral psychology examining individual decision-making explains that, "Moral judgments and decisions are often driven by automatic, affective responses, rather than explicit reasoning" [105], a fact which does not exclude the moral decisions of medical practitioners. Indeed, even when such reasoning is examined ex post facto, individuals are unlikely to change their minds on the initial decision taken [106]. Such experimental results are consonant with other studies published by neurocognitive psychologists such as Joshua Greene and Jonathan Haidt [107][108][109].…”
Section: Settling the Moral Dilemmasupporting
confidence: 82%
“…Some have suggested that reasoning over moral principles may be a better basis for decision-making (Bloom, 2016(Bloom, , 2017aSlovic, 2007). Yet people reason in a motivated fashion to reach desired conclusions (Kunda, 1990;Mercier & Sperber, 2011), and often precisely in moral contexts where reasoning is encouraged (e.g., Stanley et al, 2017). Truly objective reasoning may require effort, and be exhausting in ways that are comparable to empathy.…”
Section: What Are the Alternatives?mentioning
confidence: 99%